Continuing the Legacy of Editorial of the First Issue of Journal of Karnali Academy of Health Sciences - Aryal, Binod (Journal of Karnali Academy of Health Sciences, 2018)
Professor Dr MN Marhatta wrote in detail about the 'Milestones of Medical Education in Karnali Academy of Health Sciences' in the first issue of Journal of Karnali Academy of Health Sciences (JKAHS). By the time of this second issue of JKAHS, there has been substantial progress in achieving the goals set and plans put forward by the Academy.Two bachelor programs, i.e., Bachelor in Midwifery Sciences (BMS) and Bachelor in Public Health (BPH) studies are going to start from Mangsir 2075. Certified Anesthesia Assistant (CAA) training course is running smoothly. The Academic Council has prepared and the panel of experts has endorsed the curriculum of Masters in Obstetrics and Gynecology (MD), Masters in Orthopedics and Trauma Surgery (MS), and Masters in Anesthesiology and Critical Care (MD). Masters in General Practice and Emergency Medicine (MDGP) curriculum was prepared in the presence of experts of the various subjects, endorsed by the Academic Council of the Academy and submitted to the Nepal Medical Council (NMC) for approval and accreditation. The NMC has already agreed to take the process forward and has decided to visit KAHS for feasibility study and inspection of its preparation.KAHS is reasonably prepared to start its first Masters academic program. The Academic Council has appointed two professors in MDGP, one each in Obstetrics and Gynecology, Orthopedics, and General surgery, which is an essential and major asset for starting residency programs in the Academy. As per the criteria set by the NMC, the Academic Council has appointed the faculties in the Departments of Psychiatry and Dermatology, and the departments in Basic Medical Sciences including Anatomy, Physiology, Pharmacology, and Microbiology have been established. The class/ lecture rooms are well set up and the faculties of various department are excited and ready to welcome the first batch of MDGP residents in Jumla.There has been huge progress in the field of research and publication as well. The Nepal Health research Council has agreed to permit establishing Institutional Review Committee (IRC) in the Academy, which, we believe, will encourage the faculties and the students to participate in various national as well as locallevel scientific studies and research. There was overwhelming response from the Academy faculties as well as the faculties from various other academic institutes during the call for papers for publication in this journal.The future of Karnali Academy of Health Sciences is looking bright as this Academy was established to provide education and health services to the most marginalized people of the country. This Academy is located in a unique geography which has a huge possibility of becoming a unique institute in the field of medical education. And, this journal will continue to publish cutting-edge research and studies done in this Academy and elsewhere in the country.